Incidence of cranial asymmetry in children with a diagnosis or in investigation of Autism Spectrum Disorder (TEA) (Research, Society and Development, 2023)
The symptoms of Autistic Spectrum Disorder are often observed in the first months of life, and cranial deformities are common complaints in pediatric units and the most common form found is Positional Plagiocephaly. The objective of this study was to verify the incidence of cranial asymmetries in children diagnosed with Autistic Spectrum Disorder or under investigation. This is an exploratory-descriptive research, with a quantitative approach, which was carried out at the Physical Rehabilitation Center of the State University of Western Paraná and at the Municipal School Professora Maria dos Prazeres Neres da Silva, Cascavel - PR. The study population consisted of children between 0 and 12 years old and the following variables were evaluated: whether they had a closed diagnosis of autism or whether they were in the process of being investigated, age, gender, presence or absence of cranial asymmetry and what type of asymmetry found. After applying the inclusion criteria, 30 children diagnosed or under investigation for Autistic Spectrum Disorder were selected, 57% of whom were male. The presence of cranial asymmetries was verified in 63% of the children, namely plagiocephaly, brachycephaly and scaphocephaly. With this research it can be observed that children with the diagnosis or under investigation for Autistic Spectrum Disorder, presented important cranial alterations.